Mucuna pruriens seeds given in broiler diets on growth performance and carcass yield - Santos Ricalde, Ronald Herve; Sarmiento Franco, Luis; Lopez Santiz, Francisco; Sandoval Castro, Carlos (Ecosistemas y Recursos Agropecuarios, 2019)
The aim of this study was to evaluated the effect of soaked Mucuna pruriens (MP) seeds in tap water, acid or alkaline solution + cooking on its L-Dopa content and on the productive performance of broiler chickens. Ninety-six sexed chicks aged 21-days old with an initial live weight of 720 ± 80 g were used. Four diets were used, a control without MP (C) and three diets including 25 % MP: a) soaked MP in tap water + cooking (WMP); b) soaked MP in acetic acid solution + cooking (AAMP); c) soaked MP in calcium hydroxide solution + cooking (CHMP). The alkaline treatment reduced 71 % of L-Dopa in comparison to acid or water treatment (53 % and 41 % respectively). In the starter phase, the acid group had the lowest live weight gain (p<0.05) and highest feed conversion ratio when compared to control (p<0.05). Productive performance of birds fed with CHMP and C group was similar (p>0.05). In the finisher phase, there was not statistical difference in feed intake, live weight gain and feed conversion ratio among treatments (p>0.05). No differences were observed in carcass yield (p>0.05), but, the birds fed MP or AAMP had a heavier liver than birds on C group (p<0.05). Results shown that 25 % of CHMP can be used as feedstuff for broiler chickens without negative effects in their productive performance. Keywords: Velvet bean, L-Dopa, Poultry, weight gain.